A review of chemical and physical properties of coconut shell in asphalt mixture - Ting, Tay Lay (Penerbit UTM Press, 2016)
Coconut shell is an agricultural waste which is abundant to the environment and also rise the risk to health as well as environment. Currently, most of the researchers are investigate the use of waste material which can reduce the costof construction and increase the strength. Some of thewaste materials are used in construction for instance palm oil fuel ash, rice husk, fly ash slag, sludge, coconut shell and etc. Hence, coconut shellwas selected for this study. Generally, the chemical and physical properties of coconut shell in road construction was highlighted in this paper and compared with others raw materials. In addition, the chemical and physical characteristics of coconut shell was presented according to X-ray Fluorescence (XRF), Scanning Electron Microscopy (SEM),Fourier Transform Infrared Spectroscopy (FTIR) Analysis and X-ray Diffraction (XRD). A review of using coconut shell in asphalt mixture has better potential than others raw materials to constribute in construction field.